NANOSQUALENE CREAM FORMULA DEVELOPMENT WITH TWEEN 80 AND PEG 400 COMBINATIONS - Septiana Indratmoko; Hanifah Nurmayadah; Andi Tenri Nurwahidah (Borneo Journal of Pharmascientech, 2019)
ABSTRACT Squalene has the benefit of being an antioxidant, maintaining moisture and softness of the skin, and has an antitumor activity. Squalene has water insoluble properties and is difficult to absorb in the digestive tract so that the level of squalene in the blood is very minimal. One form of dosage that has a stable nature and can increase absorption of drugs is nanoparticle. This study aims to make nanosqualene cream that are physically stable using a combination of Tween 80 and PEG 400. The physical properties observed include organoleptic properties, homogeneity, pH, cream type, droplet size, dispersion, adhesion and viscosity. The results showed that the nanosqualen preparation could be made with a combination of Tween 80, PEG 400 and VCO (3,5:3,5:1) and 1% squalene, droplet size of 16.3 nm. Nanosqualene cream could be made using high energy methods with a combination of Tween 80, PEG 400 (9:1). Nanosqualene cream preparations have the following physical properties coconut odor, white color, semisolid form, stable, homogeneous and pH 6, O/W type, has a dispersion, adhesion and viscosity the good one. Keywords: Nanosqualen, cream, tween 80, PEG 400